Potential of Steam Pretreated Jerusalem Artichok Stem for Ethanol Production - Eliasson,Adam (2017)
To reach the goals set for the reduction of green house gas by the European Union the use of fossil fuels has to be reduced. To do this alternative fuels such as bioethanol have to substitute fossil fuels. Second generation bioethanol is produced from lignocellulosic substrates, such as forest and agricultural residues, whereas first generation bioethanol is obtained from material as sugar cane and corn containing sugar and starch. A possible raw material for production of ethanol from lignocellulosic biomass could be the stem of jerusalem artichoke. Lignocellulosic materials are recalcitrant, and therefore they need to be pretreated in order to make them more degradable. Steam pretreatment is the way of pretreatment most commonly used at commercial scale production of ethanol from lignocellulosic material. In this study, it was investigated if the stem of jerusalem artichoke is a suitable material to produce ethanol using steam pretreatment as method for pretreatment. Jerusalem artichoke stem was pretreated at 7 different conditions, and the pretreated material were subjected to enzymatic hydrolysis. Two differently pretreated material (pretreated at 200°C for 5 minutes and 10 minutes) were selected for simultaneous saccharification and fermentation. The main aim of this study was to get an as high conversion from the sugars in the raw material to ethanol as possible. The highest final ethanol yield that was received was 76% of the theoretical maximum for material treated at 200°C for 10 minutes. With this set of parameters, the corresponding overall glucan to glucose conversion was 81%. These results were approximately in the same range as those of other studies using jerusalem artichoke as raw material. The highest concentration of ethanol that was received was 10,7 g/l. This is low compared to 40 g/l which is usually considered to be what must be achieved. However, the parameters and procedure are not optimized and there is still room for improvements.
Keywords: SSF; Simultaneous Saccharification and Fermentation; Lignocellulose; Bioethanol; Second generation Bioethanol; Steam Explotion; Jerusalem Artichoke; Enzymatic Hydrolysis; chemical engineering; kemiteknik